2006
DOI: 10.1039/b600733c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of super-hydrophobic and super-oleophilic boehmite membranes from anodic alumina oxide film via a two-phase thermal approach

Abstract: The present work demonstrates a simple two-phase thermal method to prepare oriented boehmite [AlO(OH)] membranes directly from anodic alumina oxide (AAO) substrate with a copper catalyst. The acidity of the aqueous phase and reaction time play important roles in the formation of the oriented AlO(OH) membranes. Closely packed AlO(OH) crystals are parallel-aligned and vertically oriented on the substrates. The wetting properties of as-prepared oriented AlO(OH) membranes were first investigated by measuring the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In modern nanoscience, it is also widely used as a template material for the synthesis of 1D nanostructures such as metal or semiconducting nanowires 66–70. In a related context, these membranes were found to induce the orientation of various types of crystals such as apatite 71–75. As we discuss in the following, these high aspect ratio channels can also induce orientation in mesoporous phases.…”
Section: Introductionmentioning
confidence: 88%
“…In modern nanoscience, it is also widely used as a template material for the synthesis of 1D nanostructures such as metal or semiconducting nanowires 66–70. In a related context, these membranes were found to induce the orientation of various types of crystals such as apatite 71–75. As we discuss in the following, these high aspect ratio channels can also induce orientation in mesoporous phases.…”
Section: Introductionmentioning
confidence: 88%
“…The hydrophobicity of the coating can be attributed to the increased surface roughness achieved by the addition of alumina, since it is reported that the surface orientations might alter the surface O–H concentrations and surface free energy, thus altering the surface wettability 13,38. The increased water contact angle for the composite coatings in this work is ascribed to the geometry effect of the surface 21.…”
Section: Resultsmentioning
confidence: 63%
“…After anodization, aluminum oxide membranes can be removed from the aluminum substrates and use to structures other materials. Indeed, the dimension of the pores are perfect to produce aligned nanofibers after membrane dissolution 53–56. Park et al elaborated polypyrrole nanorods of various length and size by thermal evaporation of gold on one side of the membrane, its use as working electrode for the electrodeposition of polypyrrole ( Figure a, b) 53b.…”
Section: Electrochemical Oxidation Processesmentioning
confidence: 99%
“…Indeed, the dimension of the pores are perfect to produce aligned nanofibers after membrane dissolution 53–56. Park et al elaborated polypyrrole nanorods of various length and size by thermal evaporation of gold on one side of the membrane, its use as working electrode for the electrodeposition of polypyrrole ( Figure a, b) 53b. After decoration with gold nanoparticles, the surface giving rise to the best non wetting properties (θ w = 165°; α = 2°) for polypyrrole length of 9.8 μm and gold nanoparticle of 49.6 nm.…”
Section: Electrochemical Oxidation Processesmentioning
confidence: 99%